P49 Adoption of a Clinical Assessment Service in Hepatology. (20th September 2022) - Bratos, Gioia; Ovenden, William; Clark, Sarah; Forton, Daniel; Hughes, Sarah; Singanayagam, Arjuna; Yalcin, Metin
Abstract : The Hepatology Clinical Assessment Service (CAS) was established as a new service at St Georges Hospital in April 2020 during the COVID-19 pandemic. It is a novel way to assess new patients referred to the liver outpatient clinic with a view to streamlining the patient pathway, pre-investigation patients prior to a clinic appointment, avoiding inappropriate clinic appointments, rejecting inappropriate referrals, and improving the efficiency of the clinic. Hepatology CAS is a weekly consultant-led clinic supported by the Clinical Nurse Specialist (CNS) and the Patient Pathway Coordinator (PPC), the clinic happens virtually without the patient being present at the time of the triage and assessment. On average, every week 35 patients are referred to the Liver Clinic by their GPs or by other clinicians internally or externally to the hospital. Once, the patient's referral has been assessed, the CNS requests the investigations, communicates with the patient, and dictates a clinical letter to the patient and referrer, while the PPC prioritizes the appointments based on their clinical needs. Following this assessment, most of the patients then attend a face-to-face appointment, although some patients can be managed entirely virtually if clinically appropriate. With the introduction of the community non-alcoholic fatty liver pathways GP, at a similar time to this service, referrals are rejected if this pathway has not been followed. Since CAS has been introduced there have been several positive outcomes: in 2021, 18% of the referrals were appropriately repatriated to primary care with advice; 30% of the referrals were managed without needing a face-to-face appointment; the waiting time reduced from 8 weeks to 5 weeks for a clinical review, and from 16 weeks to 15 weeks for a follow-up appointment; from 2020 to 2022 the proportion of patients discharged after the first clinical review has increased from 16% to 29%; specialist treatment is instigated more quickly; patients can be discharged following their first face-to-face visit as all information is to hand, it has eliminated unnecessary follow-up and has resulted in a clear and concise pathway to refer the patients into the service, with the diagnostic tests being performed at an earlier stage In summary CAS was introduced as an urgent service response to COVID-19 but we have identified key benefits and intend to continue it.